Exploring relationship between perceived motivation factors and job satisfaction - Wahab, Eta; Shamsuddin, Alina; Abdullah, Nor Hazana (American Scientific Publishers, 2018)
A number of studies that have focused on perceived motivation factors towards employees’ job satisfaction have been conducted. However, very few relate these concepts from knowledge workers’ perspective. This paper set out to have an empirical look at the relationship between motivation factors and employees’ job satisfaction. The survey had been conducted by distributing questionnaires to employees describes as “knowledge workers” by the manager. 50 respondents participated in this study to yield a response rate of 84.75%. The results showed that only two out three motivator factors (recognition and achievement) have significant relationship between with intrinsic satisfaction and only two out of three hygiene factor (security and working condition) have significant relationship with extrinsic job satisfaction. Thus, this signifies the importance of both motivator and hygiene factors in enhancing job satisfaction among employees especially among knowledge worker.